Structural aspects of PtSn/g-Al2O3 catalysts prepared through surface controlled reactions. Behavior in the water denitrification reaction - Jaworski, María Angélica (2013)
This research focuses on the controlled preparation and characterization of PtSn/-Al2O3 catalysts and their activity and selectivity in water denitrification by reduction of NO3 − and NO2 − ions with hydrogen. The bimetallic PtSn catalysts were active in the hydrogenation of both NO3 − and NO2 − and the amount of Sn added had a pronounced influence on the activity of the catalysts, being PtSn0.25 catalyst the one with the best performance. An explanation for this behavior is given in terms of the electronic and geometric effects that the addition of tin exerts on Pt.